Utilization of Pleurotus ostreatus And Lentinus squarrosulus In The Manufacture of Mycelium-Based Biocomposite Using Sugarcane Bagasse And Cornstalk Media - Wardaya, Yasenia Sandra; Mumpuni, Aris; Ekowati, Nuraeni (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2023)
Biocomposite is a type of composite consisting of a polymer matrix material and natural fiber reinforcement. Biocomposite technology, especially natural fibers, is currently in demand. The reasons are environmentally friendly, availability of many raw materials, low production costs, biodegradable, and recyclable. Natural fibers used in the form of agricultural waste such as sugarcane bagasse and corn stalks while the mycelium of the fungus Pleurotus ostreatus and Lentinus squarrosulus are used as natural adhesives. The objectives of this research were to determine the effect of the type of white-rot fungus and the composition of the lignocellulosic material of agricultural waste that affects the quality of the resulting biocomposite board and to obtain the optimal type of white-rot fungus and the optimal composition of lignocellulosic material from agricultural waste to manufacture mycelium-based biocomposite board. The research method used a completely randomized design with ten treatments with three replications. The treatments used 2 types of mushroom (P. ostreatus and L. squarrosulus) with 2 types of Lignocellulosic materials (Sugarcane bagasse and Cornstalk) and each lignocellulosic material has 4 types of compositions (100%, 75%, 50%, and 25%). The main parameter was analyzed using Analysis of Variance (ANOVA) with an error rate of 5%, then further tested with post hoc Duncan at 95% confidence level to compare the effect between treatments. The results showed that the treatment of the type of fungus and the lignocellulosic material used affects the quality of the resulting biocomposite board. L. squarrosulus in 100% sugarcane bagasse media is the optimal type of white-rot fungus and the optimal composition of lignocellulosic material to manufacture mycelium-based biocomposite board.